DEVELOPMENT OF FLIPBOOK-BASED ENGLISH E-MODULES TO IMPROVE THE READING SKILLS OF SEVENTH GRADE JUNIOR HIGH SCHOOL STUDENTS - Arimbi Pamungkas; Tri Dewantari; Reyli Pramita (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
In the current era of the Industrial Revolution 4.0, technological developments in education continue to grow rapidly. Technology plays an important role in education. Technology is considered capable of assisting teachers in the learning process both inside and outside the classroom. Technology-based learning media continue to develop, one of which is electronic-based learning media. Flipbook-based E-modules helps teachers and students in the learning process of English both inside and outside the classroom. Through flipbook-based E-modules, teachers and students easily access materials inside and outside the classroom and encourage students to learn further materials independently. Besides, flipbook-based E-module has an interesting design so that the students do not feel bored while studying. This study aims to develop an English subject E-Module based on flipbooks to improve reading skills in seventh-grade junior high school students. This study is a research and development (R&D) study using the ASSURE model (Analyze learners; State objectives; Select methods, media, and materials; Utilize media and materials; Require learner participation; Evaluate and revise). The populations of this study were seventh-grade junior high school students. The sample was purposive sampling. The data collection techniques were interview, observation, and questionnaires. The result of the study showed that the paired sample t-test, the sig. (2-tailed) value was < 0.05, namely 0.000, which means that there was an increase in the reading skills of seventh-grade junior high school students after using the flipbook-based E-Module for English. Furthermore, based on the N Gain test results, the N-Gain score with a mean of 0.7666 is included in the high criteria. The N-Gain percentage obtained was 76.6% with an effective interpretation. Thus, it can be concluded that the flipbook-based E-Module for English is effective in improving the reading skills of seventh-grade junior high school students. The use of flipbook-based E-module as a learning media increasing the reading skill of seventh-grade junior high school students. Therefore, the flipbook-based E-Module for English can be used as a media in learning English.